2010
DOI: 10.1103/physrevlett.105.227201
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Mn-Doping Trends in Optical Properties of (Ga,Mn)As

Abstract: We report on a systematic study of optical properties of (Ga,Mn)As epilayers spanning the wide range of accessible substitutional MnGa dopings. The growth and post-growth annealing procedures were optimized for each nominal Mn doping in order to obtain films which are as close as possible to uniform uncompensated (Ga,Mn)As mixed crystals. We observe a broad maximum in the midinfrared absorption spectra whose position exhibits a prevailing blue-shift for increasing Mn-doping. In the visible range, a peak in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 15 publications
7
67
0
1
Order By: Relevance
“…Earlier IR studies of Ga 1−x Mn x As revealed a systematic red-shift of ω 0 as a function of effective carriers 9,10 . However, other more recent experiments have reported ω 0 to blue-shift with increased Mndoping 11 . We note, data reported in Ref.…”
Section: Mid-ir Peakmentioning
confidence: 79%
See 1 more Smart Citation
“…Earlier IR studies of Ga 1−x Mn x As revealed a systematic red-shift of ω 0 as a function of effective carriers 9,10 . However, other more recent experiments have reported ω 0 to blue-shift with increased Mndoping 11 . We note, data reported in Ref.…”
Section: Mid-ir Peakmentioning
confidence: 79%
“…1b we plot T C as a function of dopant concentration x of all the Ga 1−x Mn x As samples in our analysis. The samples include as-grown films investigated by Singley et al 9 , as-grown and annealed films of Burch et al 10 , annealed films of Jungwirth et al 11 , and the non-rotated as-grown and annealed samples of this work (see Table I). For the later samples presented in Fig.…”
Section: An Infrared Perspective On Trends In Tcmentioning
confidence: 99%
“…In DMS, a small fraction of magnetic ions, usually Manganese 23 , is introduced into a semiconductor. While III-V compounds such as Ga 1−x Mn x As are typically p-doped 8 and can thus exhibit carrier-mediated ferromagnetism 24 , II-VI materials such as Cd 1−x Mn x Te are found to be intrinsic and paramagnetic due to the isoelectrical incorporation of the Mn impurities.A lot of theoretical works on DMS has been devoted to the understanding of structural properties [25][26][27][28][29][30] . But in many experiments, also the spin dynamics studied via optical pump-probe experiments is of interest 17,18,31 .…”
mentioning
confidence: 99%
“…Because of the highly non-equilibrium nature of the heavily-doped ferromagnetic (Ga,Mn)As, the growth and post-growth annealing procedures have to be individually optimized for each Mn-doping level to obtain films that are as close as possible to idealized uniform (Ga,Mn)As mixed crystals with the minimal density of compensating and other unintentional defects. An extensive set of characterization measurements has to accompany the synthesis to guarantee that the materials show systematic doping trends; monitoring the thermodynamic Curie point singularities is essential for assuring the uniformity and high magnetic quality of the materials 11,15,54,55 . When omitting the above procedures, extrinsic impurities and sample inhomogeneities can yield nonsystematic doping trends and conceal the intrinsic magnetic properties of (Ga,Mn)As.…”
Section: Methodsmentioning
confidence: 99%